2016
DOI: 10.7860/jcdr/2016/21307.8276
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Potential in Adult Hypospadias

Abstract: IntrOductIOnHypospadias is a congenital anomaly of the urogenital tract which results from an arrest in normal development of urethra, foreskin and ventral aspect of the penis. The phenotype ranges from a mild degree with distal glanular meatus to severe cases with ambiguous genitalia. The incidence is 3.2 per 1000 live male births [1]. The ideal time to correct primary hypospadias is when aged 6-12 months. However, in some developing countries, such as ours, this anomaly may be left untreated until adulthood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…A few previous studies have investigated the fertility potential and birthrates in men with hypospadias . Most show a lower rate of children, although not always significant and, when available, the findings support the notion that men with proximal hypospadias have a lower fertility compared with men with distal hypospadias and controls, which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A few previous studies have investigated the fertility potential and birthrates in men with hypospadias . Most show a lower rate of children, although not always significant and, when available, the findings support the notion that men with proximal hypospadias have a lower fertility compared with men with distal hypospadias and controls, which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In other studies, semen quality in men with isolated or distal hypospadias was comparable with those of healthy controls . Nonetheless, a recent Swedish study on men with proximal hypospadias reported lower fertility as compared with individuals with distal hypospadias and controls …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…56 A recent review of 93 adults with hypospadias presenting to a reconstructive urologist highlight the long-term issues that can occur following childhood repairs, including lower urinary tract symptoms (55%) and significant rate of urethral stricture (47%), although there is a selection bias in this study. 57 Long-term sexual issues, such as erectile dysfunction, 58 ejaculatory difficulties, 59 lower self-esteem, teasing, and negative genital perception, have been reported in patients with hypospadias. 60,61 Several studies have found overall sexual function to be equivalent or slightly lower compared to controls.…”
Section: Functional Outcomes After Hypospadias Repairmentioning
confidence: 99%